SUMO-1 Modification and Its Role in Targeting the Ran GTPase-activating Protein, RanGAP1, to the Nuclear Pore Complex - Matunis, Michael J. (The Rockefeller University Press, 1998)
RanGAP1 is the GTPase-activating protein for Ran, a small ras-like GTPase involved in regulating nucleocytoplasmic transport. In vertebrates, RanGAP1 is present in two forms: one that is cytoplasmic, and another that is concentrated at the cytoplasmic fibers of nuclear pore complexes (NPCs). The NPC-associated form of RanGAP1 is covalently modified by the small ubiquitin-like protein, SUMO-1, and we have recently proposed that SUMO-1 modification functions to target RanGAP1 to the NPC. Here, we identify the domain of RanGAP1 that specifies SUMO-1 modification and demonstrate that mutations in this domain that inhibit modification also inhibit targeting to the NPC. Targeting of a heterologous protein to the NPC depended on determinants specifying SUMO-1 modification and also on additional determinants in the COOH-terminal domain of RanGAP1. SUMO-1 modification and these additional determinants were found to specify interaction between the COOH-terminal domain of RanGAP1 and a region of the nucleoporin, Nup358, between Ran-binding domains three and four. Together, these findings indicate that SUMO-1 modification targets RanGAP1 to the NPC by exposing, or creating, a Nup358 binding site in the COOH-terminal domain of RanGAP1. Surprisingly, the COOH-terminal domain of RanGAP1 was also found to harbor a nuclear localization signal. This nuclear localization signal, and the presence of nine leucine-rich nuclear export signal motifs, suggests that RanGAP1 may shuttle between the nucleus and the cytoplasm.